Is memristor a dynamic element?. Issue 24 (1st November 2013) - Bao, B.C.; Liu, Z.; Leung, H.
Abstract : Recently, it was found that flux φ and charge q are a pair of complementary basic physical attributes generating elementary circuit elements. With such a finding, two basic electrical circuit laws and constitutive relations of three fundamental circuit elements are rebuilt, upon which new dynamical equations describing dynamical circuits containing memristors are established. This leads to investigation of whether the memristor is a dynamic element.